PEMANFAATAN SARANA TEMU KEMBALI INFORMASI KHUSUSNYA KATALOG UPT PERPUSTAKAAN UNIMA OLEH MAHASISWA - Lumeno, Magdalena M.G. (ACTA DIURNA KOMUNIKASI, 2015)
Use of Meeting Facilities in Particuler Information Back Catalogue Library Unit Unima by Students. The existence of every college library is a very important tool in supporting the high university: education and teaching, training and community service, therefore Univercity library can not be separated from the duties and obligations of universitye that parent institution. According Sulistiyo Basuki (1993) argue that: library is aroom, of abuiding it self which is used to store books or other publications are usually stored according to specific arrangements to use usually stored according to specific arrangements to use the reader is not for sale. E.Martono (199:2) says that “The library is a working unit in the form of a place to collect, store, preserve library collections are maintened and systematically arranged in a cartain way to be used continuously by the wearer as a source of information. The research method used in this research is the method deskriptif.argus that Jalaludin Rachmat. This method only situations or events under study by describing and depicting the object at the same time based on facts. At the university library has function as : Storage research,educaticon, information,cultural in order to all students can determine the purpose and function of catalog as a representative summary dovument in the library catalog can also find the system thad applied in unit library UNIMA,the UNIMA library should conduct user education early in each school year to explain h-metters relating to the benefits of the use of the library. Keywords: Catalog, Library College, Student